Anticipation Overvoltage Phenomenon in EHV Overhead Lines When Connected Parallel Reactor Shunt - Imam Ghozali (Knowledge on Sustainability, Longevity, and Interdisciplinary, 2025)
The problem of increasing voltage phenomena exceeding the equipment's ability in extra-high voltage overhead line transmission is very dangerous because it damages to equipment. In general, overvoltage can occur due to lightning strikes or switching processes when there are opening and closing lines in the system. Installation of reactor shunts at the end of long lines of double circuit extra high voltage overhead lines are often used in anticipation of overvoltage caused by the influence of line capacitance. However, the installation of this shunt reactor causes another overvoltage phenomenon, reaching above 500 kV. This overvoltage phenomenon occurs when a circuit in the transmission line has not been injected but the reactor shunt has been connected. The Unenergized line gets induction and reinforcement from the second circuit which has been injected first with nominal voltage. To anticipate the occurrence of an overvoltage on the line with installed the reactor. This research was carried out in two scenarios. First, by changing the installation of the reactor which was originally connected parallel to the line then to a busbar. The second is by changing the reactor capacity. The results of the change in reactor installation to be connected to a busbar and the change in reactor shunt capacity value show that no voltage increase exceeds the nominal voltage during the energizing process. The measured voltage is below 50 kVp.